Ekspresjonizm i jego sposoby nazywania świata - Graf, Paweł (Stylistyka, 2024)
The text offers a reflection on the specificity of the existence of proper names in expressionist literature. Unlike the “classical” form, when a researcher of literary onomastics interprets a specific class of words, nomina propria, in expressionistic experience, lexemes written with a capital letter often lose their “own” meaning and become secondary or even common. Instead, ordinary words, even not self-reliant parts of speech, expressions of feelings, intellectual states, etc., distinguished in the works by the artists who create them, acquire properties. In the article, after outlining problems related to the study of the title artistic direction, the author lists its names, groups them and discusses their meaning. Thus, the category of proper name is expanded, showing how licentia poetica determines a seemingly stable research term, its scope and meaning. The research material comes from the expressionist works of Jerzy Hulewicz, Józef Wittlin and Emil Zegadłowicz.